Government House, Trinidad - (:unkn) unknown (Davidson and Todd, Ltd., Trinidad, 2009)
A picture of The Government House in St. Ann's where the foundation stone was laid in 1876. The structure is made mainly of iron and steel with local blue limestone for the front walls, the arched doorways and portico (porch) are Italian in style while the columns and railings are Victorian style.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Gardens--Trinidad and Tobago; President's House, The